2014
DOI: 10.1186/1742-2094-11-41
|View full text |Cite
|
Sign up to set email alerts
|

Activation of brain indoleamine 2,3-dioxygenase contributes to epilepsy-associated depressive-like behavior in rats with chronic temporal lobe epilepsy

Abstract: BackgroundDepression has most often been diagnosed in patients with temporal lobe epilepsy (TLE), but the mechanism underlying this association remains unclear. In this study, we report that indoleamine 2,3-dioxygenase 1 (IDO1), a rate-limiting enzyme in tryptophan metabolism, plays a key role in epilepsy-associated depressive-like behavior.MethodsRats which develop chronic epilepsy following pilocarpine status epilepticus exhibited a set of interictal disorders consistent with depressive-like behavior. Change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 39 publications
2
52
0
1
Order By: Relevance
“…In support of this notion, brain or cerebrospinal fluid concentrations of kynurenine neurotoxic metabolites are elevated in several neuropsychiatric or neurodegenerative diseases (Campbell et al, 2014;Schwarcz et al, 2001;Steiner et al, 2011;Stone et al, 2012) and have been related to the stretch of brain damages, impaired neurogenesis, and development of neuropsychiatric symptoms (Savitz et al, 2015a;Savitz et al, 2015b;Stone et al, 2012;Zunszain et al, 2012). In line with clinical findings, preclinical studies performed in rodents treated with an immune challenge have documented associations between emotional/cognitive alterations and both peripheral and brain IDO activation (Andre et al, 2008;Corona et al, 2013;Frenois et al, 2007;Gibney et al, 2013;Lawson et al, 2013;Lestage et al, 2002;Moreau et al, 2005Moreau et al, , 2008Salazar et al, 2012;Xie et al, 2014). In addition, aged mice or mice with constitutive microglial overactivation display, upon immune challenge, sustained cytokine production together with protracted brain IDO expression and depressive-like behavior (Corona et al, 2010;Godbout et al, 2008;Kelley et al, 2013).…”
Section: Neuropsychiatric Effects Of Inflammation: Evidence and Mechamentioning
confidence: 78%
See 1 more Smart Citation
“…In support of this notion, brain or cerebrospinal fluid concentrations of kynurenine neurotoxic metabolites are elevated in several neuropsychiatric or neurodegenerative diseases (Campbell et al, 2014;Schwarcz et al, 2001;Steiner et al, 2011;Stone et al, 2012) and have been related to the stretch of brain damages, impaired neurogenesis, and development of neuropsychiatric symptoms (Savitz et al, 2015a;Savitz et al, 2015b;Stone et al, 2012;Zunszain et al, 2012). In line with clinical findings, preclinical studies performed in rodents treated with an immune challenge have documented associations between emotional/cognitive alterations and both peripheral and brain IDO activation (Andre et al, 2008;Corona et al, 2013;Frenois et al, 2007;Gibney et al, 2013;Lawson et al, 2013;Lestage et al, 2002;Moreau et al, 2005Moreau et al, , 2008Salazar et al, 2012;Xie et al, 2014). In addition, aged mice or mice with constitutive microglial overactivation display, upon immune challenge, sustained cytokine production together with protracted brain IDO expression and depressive-like behavior (Corona et al, 2010;Godbout et al, 2008;Kelley et al, 2013).…”
Section: Neuropsychiatric Effects Of Inflammation: Evidence and Mechamentioning
confidence: 78%
“…In addition, aged mice or mice with constitutive microglial overactivation display, upon immune challenge, sustained cytokine production together with protracted brain IDO expression and depressive-like behavior (Corona et al, 2010;Godbout et al, 2008;Kelley et al, 2013). More importantly, pharmacological or genetic inhibition of IDO prevents the development of depressive-/anxiety-like behaviors and cognitive impairments (Barichello et al, 2013;Henry et al, 2009;O'Connor et al, 2009a;O'Connor et al, 2009b;O'Connor et al, 2009c;Salazar et al, 2012;Xie et al, 2014). Conversely, systemic kynurenine administration dose-dependently impairs emotional behaviors and spatial memory (Alexander et al, 2012;Chess et al, 2009;O'Connor et al, 2009c;Salazar et al, 2012).…”
Section: Neuropsychiatric Effects Of Inflammation: Evidence and Mechamentioning
confidence: 99%
“…In 2014, Xie et al [17] found the expression of IL-1β and IL-6 in the hippocampus of depressed and epileptic rats that that IL-1β mRNA increased 3 weeks after status epilepticus, while IL-6 mRNA increased 6 weeks after status epilepticus.…”
Section: Neuroinflammationmentioning
confidence: 97%
“…Depressive behavior tests showed a taste preference that represents anhedonia symptoms in depression; immobility time was prolonged in a forced swimming test (FST), which is the equivalent of a depressive-like state [17]. Depression improves in epileptics undergoing disarticulation or resection of epileptic foci, resulting in decreased seizures and epileptiform activities.…”
mentioning
confidence: 99%
“…Так, в экспериментах на крысах Wistar с индуцированным пилокарпином эпилепти-ческим статусом W. Xie и соавт. [16] было установле-но через 3-6 нед развитие состояния, являющегося эквивалентом депрессии (развитие ангедонии и уве-личение времени неподвижности при проведении теста принудительного плавания). Аналогичные ре-зультаты на крысах Wistar были получены S. Chen и соавт.…”
unclassified